Effect of branched-chain amino acid ingestion on moderate and high intensity cycling - Foster, C.; Faria, E.; Chinevere, T.; Faria, I. (Medicine & Science in Sports & Exercise, 1998)
The hypothesis that branched-chain amino acid (BCAA) supplements reduce brain serotonin synthesis resulting in increased time to exhaustion, increased work output, and reduced perception of effort (RPE) was tested. Endurance-trained cyclists (M = 16; F = 4) rode several times for 60 minutes at 70-75% VO2max after ingesting the following: A -- 25 gm of placebo; B -- 25 gm CHO gel plus BCAA (8.8 mg valine, 18 mg leucine, 6.3 mg isoleucine); and C -- 25 gm CHO gel plus BCAA (99 mg valine, 368 mg leucine, <20 mg isoleucine). No significant differences in time to exhaustion, work output, or RPE were evidenced between conditions. However, when B and C conditions were combined 11 Ss demonstrated improved endurance capacity when compared to the placebo condition. No significant difference was found for post-exercise blood glucose or lactic acid levels. Implication. BCAA ingestion does not improve performance of groups of cyclists. Some individuals demonstrate minor improvements in endurance performance after BCAA ingestion.